PENGARUH PENGUMUMAN EMPLOYEE STOCK OPTION PROGRAM TERHADAP REAKSI PASAR DAN KINERJA PERUSAHAAN PADA PERUSAHAAN PUBLIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Selvy Chelarci Letlora (Journal of Business & Banking, 2012)
The relationship between management's interest as an agent and company owner's interest as a principal sometimes can be different, in which it is familiar to Agency Problems. In addition, business innovations have been created to increase or creating value of the firm and reducing the agency problems, for example the Employee Stock Option Program (ESOP) to solve the problem. This research tries to analyze the application of ESOP and its influence toward the market's reaction and the corporate performance around its announcement to public in January 1, 2006 - December 31, 2007. To analyze the market's reaction, researcher use event study method, and ROA, ROE, TATO, EPS, PER, NPM, and Sales Growth (SG) for the company's performance. Next, it analyzes the market's reaction around its announcement with one sample t-test and uses eleven days as event windows (t-5 until t+5). For the corporate performance, researcher wes paired samples t-test, special for the corporate performance, with two steps. The first step is to compare the indicators of company's performance one year before its anouncement and one year after, and the second step is to compare the indicators of company's performance one year before its announcement and two year after. The results of this research show that there is no positive significant abnormal return around its announcement, and for the company's performance after its announcement, in general, not higher than company's performance before the announcement.